Keberhasilan Pembangunan dengan Menjaga Lingkungan Di Kelurahan Negeri Olok Gading Kecamatan Teluk Betung Barat Kota Bandar Lampung - Lies Kumara Dewi; Eka Ubaya Taruna Rauf; Husna Purnama (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Development must be carried out in every nation. Change from bad to better is development. There is a close relationship between development and the surrounding environment. Development affects the environment and is influenced by the environment. Development will be successful if the environment is maintained, such as not littering, not cutting down trees, planting trees, and sorting waste. Environmental sustainability can only be achieved through environmental protection. As development actors, the environment that is not maintained and cared for will be damaged and can result in various disasters such as floods, erosion, and other threats to human life. Likewise, when the rainy season begins in Bandar Lampung City, floods occur everywhere. This is because there are still many people who do not know how important it is to protect the environment. One example is throwing garbage in the river so that it clogs the flow of the river and garbage is thrown away in the wrong place. With this community service, it is hoped that the community will be more aware of the need to protect the environment by not littering, not cutting down trees, and sorting waste